Apologetic Strategies of ESL Urdu Students: A Study Based on Formal and Informal Socio-Pragmatic Contexts (Journal of Social Sciences Review, 2025)
The main concern of this paper is to investigate different apologetic strategies in the English language of ESL students who were natives of the Urdu language (n=30), selected through a purposive sampling technique. How differently an apology can be performed in different socio-pragmatic ESL contexts has been investigated based on the context, level of seriousness, and nature of the offense. For this purpose, 'Speech Act Theory' was employed, as proposed by Langshaw Austin (1962). The methodological procedure was informed by the study of Blum-Kulka (1989), in which data was categorized under Blum-Kulka's taxonomy by considering formal and informal apologetic contexts linguistically. Two instruments have been used: a) a questionnaire to estimate the awareness of respondents' preference for apology in different contexts, and b) a Discourse Completion Task (DCT) based on eight formal and informal situations adopted from the study of Shoshana et al. (1989). It was followed by an interview to see the views of respondents about apologetic strategies in the Urdu language. Quantitative analysis of the data was done with IBM SPSS (V21) to calculate mean values (M) and percentages (%) of different taxonomical categories. Findings reveal the minor difference in apologetic strategies in formal and informal contexts. It highlights the awareness of Urdu ESL speakers of performing an apology with more than one strategy based on the context, level of seriousness, and nature of the offense. The highest percentage was for apologies using Illocutionary Force Indicating Devices (IFIDs). On the other hand, respondents intended to apologize in English rather than Urdu, as per the majority's views. The study signifies the importance of communicative competence, which ensures the appropriateness of utterance as per the need and situation.
Keywords: Apology; Speech Act; Pragmatics; Apologetic Strategies